Chinese Herbs Interfering with Cancer Reprogramming Metabolism. (5th May 2016) - Zhong, Zhangfeng; Qiang, William W.; Tan, Wen; Zhang, Haotian; Wang, Shengpeng; Wang, Chunming; Qiang, Wenan; Wang, Yitao
Abstract : Emerging evidence promotes a reassessment of metabolic reprogramming regulation in cancer research. Although there exists a long history of Chinese herbs applied in cancer treatment, few reports have addressed the effects of Chinese herbal components on metabolic reprogramming, which is a central cancer hallmark involved in the slowing or prevention of chemoresistance in cancer cells. In this review, we have focused on four core elements altered by metabolic reprogramming in cancer cells. These include glucose transport, glycolysis, mitochondrial oxidative phosphorylation, and fatty acid synthesis. With this focus, we have summarized recent advances in metabolic reprogramming of cancer cells in response to specific Chinese herbal components. We propose that exploring Chinese herbal interference in cancer metabolic reprogramming might identify new therapeutic targets for cancer and more ways in which to approach metabolism-related diseases.